Sheet, and manufacturing method of sheet

A fluororesin-based sheet with excellent gas barrier properties is achieved through a multi-layer structure of polyamide resin, melt-formable perfluoropolymer, and fluororesin with adhesive functional groups, addressing the need for enhanced gas barrier performance while maintaining the unique properties of fluororesins.

JP2025052818APending Publication Date: 2025-04-07AGC INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023161734
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-04-07

AI Technical Summary

Technical Problem

There is a need for a fluororesin-based sheet with excellent gas barrier properties, which can leverage the unique properties of fluororesins while maintaining the integrity of the sheet.

Method used

A multi-layer sheet structure comprising a first layer of polyamide resin, a second layer of melt-formable perfluoropolymer with tetrafluoroethylene-based units, and an intermediate layer of fluororesin with adhesive functional groups, where the average roughness of the interface between the first and intermediate layers is 5 μm or less.

Benefits of technology

The sheet achieves excellent gas barrier properties due to the combination of polyamide resin and perfluoropolymer layers, with the intermediate layer enhancing adhesion without compromising the properties of the second layer, thereby preventing uneven thickness and reduced gas barrier performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025052818000001
    Figure 2025052818000001
Patent Text Reader

Abstract

To provide a fluororesin-based sheet exhibiting an excellent gas barrier property, and a manufacturing method of the sheet.SOLUTION: A sheet comprising a first layer containing a polyamide resin, a second layer including a unit based on tetrafluoroethylene and containing a melt-moldable perfluoro polymer, and an intermediate layer containing a fluororesin containing an adhesive functional group. An average roughness on an interface between the first layer and the intermediate layer is 5 μm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a sheet and a method for making the sheet. [Background technology]

[0002] Fluorine resins are used in various fields because of their excellent physical properties such as electrical characteristics, water and oil repellency, chemical resistance, heat resistance, etc. In particular, tetrafluoroethylene-based polymers are excellent in physical properties such as mold releasability, electrical insulation, water and oil repellency, chemical resistance, weather resistance, heat resistance, etc., and are used by being processed into various molded articles. There is a demand for a sheet that has gas barrier properties while taking advantage of the inherent properties of such fluororesins. Polyamide resins have been considered as materials with excellent gas barrier properties (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-077193 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of one embodiment of the present disclosure is to provide a fluororesin-based sheet having excellent gas barrier properties, and a method for producing the sheet. [Means for solving the problem]

[0005] The present disclosure includes the following aspects. <1> A first layer containing a polyamide-based resin; a second layer containing a perfluoropolymer that includes units based on tetrafluoroethylene and is melt-fabricable; and an intermediate layer containing a fluororesin having an adhesive functional group, A sheet, wherein the average roughness of the interface between the first layer and the intermediate layer is 5 μm or less. <2> The arithmetic mean roughness Ra of the outer surface of the first layer is 5 μm or less. <1> The sheet described in. <3> The average total thickness is 1 μm to 3 mm. <1> or <2> The sheet described in. <4> the adhesive functional group is at least one selected from the group consisting of a carbonyl group-containing group, a hydroxy group, an epoxy group, an amide group, an amino group, an isocyanate group, a glycidyl group, a cyano group, a silyl group, and a silanate group; <1> ~ <3> A sheet described in any one of the above. <5> The polyamide-based resin includes at least one selected from the group consisting of polyamide 6, polyamide 12, and polyamide 6 / polyamide 12 copolymer. <1> ~ <4> A sheet described in any one of the above. <6> The perfluoropolymer has a main chain carbon number of 1×10 6 There are 50 or less adhesive functional groups per unit area. <1> ~ <5> A sheet described in any one of the above. <7> The ratio of the average thickness of the first layer to the average total thickness of the sheet is 0.30 to 0.80. <1> ~ <6> A sheet described in any one of the above. <8> The melt constituting the first layer, the melt constituting the intermediate layer, and the melt constituting the second layer are co-extruded from a die; <1> ~ <7> 13. A method for producing the sheet according to any one of claims 1 to 12. <9> the temperature of the die is set to a temperature equal to or higher than the highest melting point among the melting point of the perfluoropolymer, the melting point of the polyamide resin, and the melting point of the fluororesin having an adhesive functional group, and the difference from the highest melting point is set to a temperature within 50° C.; <8> A method for producing the sheet according to claim 1. <10> The cooling rate is 5 to 35°C / sec. <8> or <9> A method for producing the sheet according to claim 1. Effect of the Invention

[0006] According to one embodiment of the present disclosure, it is possible to provide a fluororesin-based sheet having excellent gas barrier properties and a method for producing the sheet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] In the present disclosure, a numerical range indicated using "~" means a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when there are multiple substances corresponding to each component, the amount of each component means the total amount of the multiple substances, unless otherwise specified. In the present disclosure, the term "fluororesin" refers to a resin having fluorine atoms in the molecule. In this disclosure, the term "unit" refers to a portion derived from a monomer that exists in a polymer and constitutes the polymer. The term "unit" also refers to a unit that is obtained by chemically converting the structure of a unit after the formation of a polymer. In some cases, units derived from individual monomers are referred to by the name of the monomer with "unit" added. The average thickness of each layer indicates the thickness at room temperature (25° C.), and is the average value of measurements taken at any five points using a micrometer.

[0008] <Sheet> The sheet of the present disclosure comprises a first layer containing a polyamide resin, a second layer containing a perfluoropolymer that contains units based on tetrafluoroethylene and is melt-formable, and an intermediate layer containing a fluororesin having adhesive functional groups, and the average roughness of the interface between the first layer and the intermediate layer is 5 μm or less. The sheet having the above-mentioned structure has excellent gas barrier properties, the reason for which is presumed to be as follows.

[0009] The gas barrier property is improved by laminating a first layer containing a polyamide resin having excellent gas barrier properties to a second layer containing a perfluoropolymer containing a unit based on tetrafluoroethylene, which exhibits the properties unique to fluororesins. Then, by laminating these layers via an intermediate layer containing a fluororesin having an adhesive functional group, the properties of the second layer can be maintained without impairing the properties of the second layer. Here, it has been revealed that if the interface between the first layer and the intermediate layer is rough, the thickness of the first layer having excellent gas barrier properties becomes uneven, and the gas barrier property at the thin part is reduced. This tendency is more pronounced as the thickness of the first layer and the thickness of the entire sheet become thinner. In the sheet of the present disclosure, the average roughness of the interface between the first layer and the intermediate layer is 5 μm or less, so that the occurrence of such defects is suppressed. Each layer of the laminate will now be described.

[0010] [First layer] The first layer contains a polyamide resin. Examples of the polyamide resin include aliphatic polyamide resins and aromatic polyamide resins. The polyamide resins may be used alone or in combination of two or more.

[0011] Specifically, the polyamide resin preferably includes at least one selected from the group consisting of polyamide 12, polyamide 6, polyamide 66, polyamide 46, polyamide 11, polyamide MXD6 (semi-aromatic polyamide), polyamide 26, polyamide 69, polyamide 610, polyamide 611, polyamide 612, polyamide 6T, polyamide 6I, polyamide 912, polyamide 1012, polyamide 1212, polyamide PACM12, etc., and more preferably includes at least one selected from the group consisting of polyamide 6, polyamide 12, and polyamide 6 / polyamide 12 copolymer. Furthermore, when a polyamide 6 / polyamide 12 copolymer is used as the polyamide-based resin, a copolymer having a relatively high content of polyamide 6 is preferred from the viewpoint of gas barrier properties, and for example, one having a molar ratio (polymerization ratio) of polyamide 6 to polyamide 12 within the range of 7:3 to 9:1 is more preferred.

[0012] From the viewpoint of heat resistance, the melting point of the polyamide resin is preferably 180° C. or higher, and more preferably 190° C. or higher. From the viewpoint of ease of processing, the melting point of the polyamide resin is preferably 320° C. or lower, and more preferably 310° C. or lower.

[0013] The first layer may contain components other than the polyamide-based resin as long as the effects of the present disclosure are not impaired. Examples of other components include thermoplastic resins such as fluororesins, and additives. Examples of the additives include plasticizers, heat-resistant materials, foaming agents, weathering agents, crystal nucleating agents, crystallization accelerators, release agents, lubricants, antistatic agents, flame retardants, flame retardant assistants, pigments, dyes, and other functionality-imparting agents.

[0014] The average thickness of the first layer is preferably 10 to 2000 μm, more preferably 20 to 1000 μm, further preferably 50 to 600 μm, particularly preferably 50 to 400 μm, and extremely preferably 60 to 160 μm. When the average thickness of the first layer is equal to or greater than the lower limit of the above range, the gas barrier property is more excellent. When the average thickness of the first layer is equal to or less than the upper limit of the above range, the flexibility of the sheet is excellent.

[0015] From the viewpoint of further improving the gas barrier property, the ratio of the average thickness of the first layer to the average total thickness of the sheet is preferably 0.30 to 0.80, more preferably 0.35 to 0.75, even more preferably 0.40 to 0.70, and even more preferably 0.40 to 0.60. stomach.

[0016] From the viewpoint of superior gas barrier property, the arithmetic mean roughness Ra of the outer surface of the first layer is preferably 5 μm or less, more preferably 4 μm or less, further preferably 3 μm or less, and particularly preferably 2 μm or less. The arithmetic mean roughness Ra is measured in accordance with JIS B 0601:2013.

[0017] [Second Layer] The second layer contains a perfluoropolymer which includes units based on tetrafluoroethylene (hereinafter also referred to as "TFE") (hereinafter also referred to as "TFE units") and is melt-processable. The perfluoropolymers may be used alone or in combination of two or more kinds.

[0018] The content of the TFE unit in the perfluoropolymer is preferably 50 mol% or more, more preferably 90 mol% or more, and even more preferably 95 mol% or more, based on the total units in the perfluoropolymer, from the viewpoint of favorably exhibiting the characteristics due to the TFE unit. The content may be 99 mol% or less, or 98 mol% or less.

[0019] The perfluoropolymer can be melt molded. From the viewpoint of heat resistance, the melting point of the perfluoropolymer is preferably 200° C. or higher, more preferably 260° C. or higher. From the viewpoint of ease of processing, the melting point of the perfluoropolymer is preferably 325° C. or lower, more preferably 320° C. or lower. In this disclosure, "melting point" means the temperature corresponding to the maximum value of the melting peak measured by differential scanning calorimetry (DSC).

[0020] The difference between the melting point of the perfluoropolymer contained in the second layer and the melting point of the polyamide resin contained in the first layer is preferably within 150°C, more preferably within 130°C, and even more preferably within 120°C.

[0021] The perfluoropolymer is preferably a polymer (PFA) containing TFE units and units based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE units), or a polymer (FEP) containing TFE units and units based on hexafluoropropylene (HFP), with PFA being particularly preferred from the viewpoint of properties such as adhesiveness, processability, etc. These polymers may further contain units based on other comonomers. PAVE is preferably CF2=CFOCF3, CF2=CFOCF2CF3 or CF2=CFOCF2CF2CF3 (hereinafter also referred to as "PPVE"), and more preferably PPVE.

[0022] When the perfluoropolymer contains PAVE units, the content of the PAVE units relative to the total content of the TFE units and the PAVE units is preferably 0.1 to 10.0 mol %, more preferably 0.5 to 7.0 mol %, and even more preferably 1.0 to 5.0 mol %, from the viewpoint of heat resistance. When the perfluoropolymer contains HFP units, the content of the HFP units relative to the total content of the TFE units and the HFP units is preferably 1.0 to 15.0 mol %, more preferably 1.0 to 13.0 mol %, and even more preferably 1.0 to 11.0 mol %, from the viewpoint of heat resistance.

[0023] Perfluoropolymers have an adhesive functional group content of 1×10 6 It is preferable that the number of the adhesive functional groups is 50 or less per one.

[0024] The second layer may contain components other than the perfluoropolymer as long as the effects of the present disclosure are not impaired. Examples of other components include known resin additives, polyamides, amino group-containing polymers, fluorine-containing elastomers (fluororubbers having VDF units, fluororubbers having propylene units and TFE units, etc.) and crosslinked products thereof, and resin particles (polytetrafluoroethylene particles, polyether ether ketone particles, polyphenylene sulfide particles, etc.).

[0025] The content of the perfluoropolymer in the second layer is preferably 5 to 100 mass%, more preferably 20 to 100 mass%, further preferably 50 to 100 mass%, and particularly preferably 70 to 100 mass%, of the materials constituting the layer (100 mass%).

[0026] The average thickness of the second layer is preferably 1 to 1000 μm, more preferably 5 to 700 μm, further preferably 10 to 500 μm, and particularly preferably 10 to 200 μm. When the average thickness of the second layer is equal to or greater than the lower limit of the above range, the properties specific to the fluororesin are easily exhibited. When the average thickness of the second layer is equal to or less than the upper limit of the above range, the flexibility of the sheet is excellent.

[0027] From the viewpoint of the balance of each characteristic, the ratio of the average thickness of the second layer to the average thickness of the first layer is preferably from 0.04 to 2.00, more preferably from 0.05 to 1.50, further preferably from 0.07 to 1.25, and particularly preferably from 0.17 to 1.25.

[0028] [Middle class] The intermediate layer contains a fluororesin having an adhesive functional group (hereinafter, also referred to as "fluororesin (A)"). In the present disclosure, the term "fluororesin having adhesive functional groups" does not include cases in which the adhesive functional groups are derived from a polymerization initiator or a chain transfer agent and are present only at the terminals.

[0029] The adhesive functional group may be at least one selected from the group consisting of a carbonyl group-containing group, a hydroxy group, an epoxy group, an amide group, an amino group, an isocyanate group, a glycidyl group, a cyano group, a silyl group, and a silanate group. Examples of the carbonyl group-containing group include a group having a carbonyl group between carbon atoms of a hydrocarbon group, a carbonate group, a carboxy group, a haloformyl group, an alkoxycarbonyl group, a carboxy ester group, and an acid anhydride group. The adhesive functional group is preferably a carboxy group or an acid anhydride group from the viewpoint of excellent adhesiveness.

[0030] The adhesive functional group possessed by the fluororesin (A) may be derived from a monomer having an adhesive functional group, or may be further present in a terminal group derived from a polymerization initiator or a chain transfer agent. The adhesive functional group of the fluororesin (A) may be introduced by a surface treatment, such as a known method including a corona discharge treatment and a plasma treatment (excluding the corona discharge treatment). The content of adhesive functional groups in the fluororesin (A) is 1 × 10 6 The number of particles is preferably 100 to 50,000, and more preferably 500 to 10,000. The proportion of units derived from a monomer having an adhesive functional group relative to all units in the fluororesin (A) is preferably from 0.01 to 5 mol %, particularly preferably from 0.05 to 1 mol %.

[0031] As the fluororesin (A), it is preferable that it contains a copolymer having units derived from tetrafluoroethylene, units derived from perfluoro(alkyl vinyl ether), and units derived from a monomer having an adhesive functional group (hereinafter also referred to as "adhesive PFA"), because it has excellent adhesion and excellent formability into films, etc.

[0032] As the monomer having an adhesive functional group, a monomer having a carboxy group, an acid anhydride group or a carboxylic acid halide group is preferable, and an unsaturated dicarboxylic acid anhydride is more preferable. Examples of the carboxylic acid anhydride include itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride (himic acid anhydride), and maleic anhydride. The monomer having an adhesive functional group may have one type of adhesive functional group alone, or may have two or more types of adhesive functional groups.

[0033] The adhesive PFA may contain units derived from other monomers than TFE, perfluoro(alkyl vinyl ether), and monomers having adhesive functional groups, as necessary. Examples of other monomers include fluoroolefins (excluding tetrafluoroethylene).

[0034] Specific examples of adhesive PFA include "PFA having functional group i" described in WO 2019 / 203243.

[0035] The melting point of the fluororesin (A) is preferably 200° C. or higher, more preferably 250° C. or higher, and even more preferably 280° C. or higher.

[0036] The melting point of the fluororesin (A) is preferably 350°C or lower, more preferably 320°C or lower. From the viewpoint of enhancing the adhesiveness of the intermediate layer, the melting point of the fluororesin (A) is preferably 300°C or lower, more preferably 280°C or lower, and more preferably 250°C or lower. When the melting point of the fluororesin (A) is equal to or lower than the upper limit of the above range, a sheet that is a laminate can be produced at a relatively low temperature. Therefore, deformation due to heating during production of the sheet is suppressed, and wrinkles and breakage of the sheet are suppressed.

[0037] From the viewpoint of keeping low the average roughness of the interface between the intermediate layer and the first layer, the difference between the melting point of the fluororesin (A) contained in the intermediate layer and the melting point of the polyamide resin contained in the first layer is preferably within 130°C, more preferably within 120°C, and even more preferably within 110°C.

[0038] The intermediate layer may contain components other than the fluororesin (A) as long as the effects of the present disclosure are not impaired. Examples of other components include known resin additives, fluororesin having no adhesive functional group (hereinafter also referred to as "fluororesin (B)"), polyamide, amino group-containing polymer, fluorine-containing elastomer (fluororubber having VDF units, fluororubber having propylene units and TFE units, etc.) and crosslinked products thereof, resin particles (polytetrafluoroethylene particles, polyether ether ketone particles, polyphenylene sulfide particles, etc.), and the like. The fluororesin (B) may be the perfluoropolymer described in the second layer.

[0039] The proportion of the fluororesin (A) in the intermediate layer is preferably 5 to 100 mass%, more preferably 20 to 100 mass%, further preferably 50 to 100 mass%, particularly preferably 70 to 100 mass%, of the materials constituting the layer (100 mass%). When the proportion of the fluororesin (A) in the intermediate layer is equal to or more than the lower limit of the above range, the adhesion and heat resistance are further improved.

[0040] The average roughness of the interface between the first layer and the intermediate layer is 5 μm or less, preferably 4 μm or less, more preferably 3 μm or less, and even more preferably 2 μm or less. The average roughness of the interface between the first layer and the intermediate layer is a value measured by observing the cross section using a scanning electron microscope (SEM), and the arithmetic average roughness is measured in accordance with JIS B0633:2001.

[0041] The average thickness of the intermediate layer is preferably 1 to 700 μm, more preferably 5 to 500 μm, and even more preferably 10 to 100 μm. When the average thickness of the intermediate layer is equal to or greater than the lower limit of the above range, the adhesiveness is excellent and the occurrence of peeling between layers tends to be suppressed. When the average thickness of the intermediate layer is equal to or less than the upper limit of the above range, the flexibility of the sheet is excellent.

[0042] The ratio of the average thickness of the intermediate layer to the average thickness of the first layer is preferably from 0.04 to 2.00, more preferably from 0.05 to 1.50, further preferably from 0.07 to 1.25, and particularly preferably from 0.17 to 1.25.

[0043] The ratio of the average thickness of the intermediate layer to the average thickness of the second layer is preferably 0.2 to 5.0, more preferably 0.3 to 3.0, and even more preferably 0.5 to 2.0.

[0044] The average total thickness of the sheet is preferably 1 μm or more, more preferably 50 μm or more, and even more preferably 100 μm or more. The average total thickness of the sheet is preferably 3 mm or less, more preferably 2 mm or less, and even more preferably 500 μm or less. In particular, when the total thickness is thin, the effect of the gas barrier property is more pronounced when the average roughness of the interface between the first layer and the intermediate layer described below is 5 μm or less.

[0045] [Gas barrier properties] The oxygen permeability of the sheet is 2.0×10 5 cm 3 cm / (cm 2 ·S·Pa) or less is preferable, and 1.5×10 5 cm 3 cm / (cm 2 ·S·Pa) or less is more preferable, and 1.25×10 5 cm 3 cm 3 cm / (cm 2 ·S·Pa) or less is even more preferable.

[0046] The oxygen permeability coefficient of the sheet is measured in accordance with JIS K7126-1:2006 (differential pressure method) using a differential pressure gas permeability measuring device (for example, a differential pressure gas permeability measuring device manufactured by MORESCO) at a test temperature of 40° C. and oxygen of 1 atm.

[0047] [Method of manufacturing sheet] The sheet of the present disclosure may be produced by any method, as long as the above-mentioned configuration is obtained. Examples of the method include extrusion molding, extrusion lamination, heat lamination, dry lamination, etc. In the extrusion molding method, a resin is extruded from a mold (die) disposed downstream of an extruder to form a sheet. Since the sheet of the present disclosure is a multi-layer laminate, a co-extrusion molding method may be applied in which melts of multiple resins constituting each layer are co-extruded from a die to obtain a laminate all at once.

[0048] In the co-extrusion molding method, the die temperature is preferably set to a temperature equal to or higher than the highest melting point (hereinafter also referred to as the maximum melting point) among the melting points of the polyamide resin contained in the first layer, the perfluoropolymer contained in the second layer, and the fluororesin (A) contained in the intermediate layer. From the viewpoint of sufficient melting of the perfluoropolymer, the polyamide resin, and the fluororesin (A) in the die, the die temperature is preferably set to a temperature 10°C or higher than the maximum melting point, more preferably 20°C or higher.

[0049] Generally, the melting point of a polyamide resin is lower than the melting points of the perfluoropolymer and the fluororesin (A). Therefore, the higher of the melting point of the perfluoropolymer and the melting point of the fluororesin (A) may be interpreted as the maximum melting point of the die temperature.

[0050] On the other hand, if the difference between the die temperature and the maximum melting point is too high, the polymer and resin will mix at the interface of each layer, making the interface less smooth. Therefore, the difference between the die temperature and the maximum melting point is preferably 60°C or less, more preferably 55°C or less, even more preferably 50°C or less, and particularly preferably 45°C or less.

[0051] Immediately after the laminate is extruded from the die and formed, the first layer and the second layer are cooled and solidified from the outside, and the intermediate layer disposed inside is the most difficult to cool. Since the melting point of the polyamide resin is generally lower than the melting point of the perfluoropolymer and the melting point of the fluororesin (A), the perfluoropolymer and the fluororesin (A) start to solidify before the polyamide resin. In other words, the second layer tends to solidify first, followed by the intermediate layer, and the first layer tends to solidify the slowest. Due to the difference in the timing of solidification, the interface between the first layer and the intermediate layer is likely to become rough. However, when the die temperature is set within the above range, the difference in solidification rate between the polyamide resin and the perfluoropolymer and fluororesin (A) is appropriately suppressed, so that the average roughness of the interface between the first layer and the intermediate layer tends to be kept low.

[0052] Specifically, the die temperature is preferably 360° C. or less, more preferably 350° C. or less, and even more preferably 345° C. or less.

[0053] The cooling rate is preferably 5° C. / sec or more, more preferably 7.5° C. / sec or more, and even more preferably 10° C. / sec or more, and is preferably 35.0° C. / sec or less, more preferably 34.5° C. / sec or less, and even more preferably 34.0° C. / sec or less. When the cooling rate is equal to or higher than the lower limit of the range, the adhesion of the molten material to the roll provided downstream of the die is suppressed, and the surface roughness tends to be suppressed.When the cooling rate is equal to or lower than the upper limit of the range, the difference in the solidification rate between the first layer and the intermediate layer is appropriately suppressed, and the average roughness of the interface between the first layer and the intermediate layer tends to be suppressed.In addition, when the cooling rate is equal to or lower than the upper limit of the range, the solidification rate near the surface is prevented from becoming too fast compared to the solidification rate inside, and therefore deformation such as warping of the film tends to be suppressed, and peeling between each layer tends to be suppressed.

[0054] In the present disclosure, the cooling rate is determined by dividing the difference between the temperature of the melt immediately after passing through the die and the temperature of the sheet immediately after passing through a roll provided downstream of the die by the passage time.

[0055] It is desirable to appropriately adjust the screw rotation speed of the extruder for the molten material constituting the first layer, the screw rotation speed of the extruder for the molten material constituting the second layer, and the screw rotation speed of the extruder for the molten material constituting the intermediate layer according to the respective intended thicknesses. For example, the screw rotation speed of the extruder for the molten material constituting the first layer is preferably 2.50 rpm or more, more preferably 3.75 rpm or more, and even more preferably 5.00 rpm or more. The screw rotation speed of the extruder for the molten material constituting the first layer is preferably 300 rpm or less, more preferably 200 rpm or less, and even more preferably 150 rpm or less.

[0056] The screw rotation speed of the extruder for the molten material constituting the second layer is preferably 1.00 rpm or more, more preferably 1.25 rpm or more, and even more preferably 1.50 rpm or more. The screw rotation speed of the extruder for the molten material constituting the second layer is preferably 200 rpm or less, more preferably 100 rpm or less, and even more preferably 50 rpm or less.

[0057] The screw rotation speed of the extruder for the molten material constituting the intermediate layer is preferably 1.00 rpm or more, more preferably 1.25 rpm or more, and even more preferably 1.50 rpm or more. The screw rotation speed of the extruder for the molten material constituting the intermediate layer is preferably 200 rpm or less, more preferably 100 rpm or less, and even more preferably 50 rpm or less.

[0058] The sheet winding speed is preferably 0.1 m / min or more, more preferably 0.15 m / min or more, and even more preferably 0.2 m / min or more. The sheet winding speed is preferably 2 m / min or less, more preferably 1.5 m / min or less, and even more preferably 1 m / min or less. EXAMPLES

[0059] The present disclosure will be described in detail below with reference to examples, but the present disclosure is not limited thereto. Examples 1 to 12 are working examples, and Examples 13 to 16 are comparative examples.

[0060] [Example 1] As the polyamide resin for the first layer, nylon 612 (7034B, manufactured by Ube Industries, Ltd., melting point: 215° C., melt flow rate: 10.1 g / 10 min) was prepared. As the perfluoropolymer for the second layer, a TFE / perfluoro(alkyl vinyl ether) copolymer (manufactured by AGC, Fluon (registered trademark), PFA P-63P, melting point: 305° C., melt flow rate: 13.0 g / 10 min) was prepared. In addition, as a fluororesin having adhesive functional groups, PFA1 was polymerized in a ratio of TFE / CF2=CF-O-(CF2)3F / hymic anhydride=97.9 / 2.0 / 0.1 (mol%) in the same manner as in Example 5 of WO2015 / 182702. The melting point of PFA1 was 300°C, and the melt flow rate was 11.0g / 10min.

[0061] The above materials were co-extruded to obtain a three-layer film. The extruder screw speed, melt temperature, die temperature, roll temperature, take-up speed, and cooling rate were set under the conditions shown in Table 1.

[0062] The average thickness of each layer, the average roughness of the interface between the first layer and the intermediate layer, and the arithmetic mean roughness Ra of the outer surface of the first layer were measured by the above-mentioned method. The arithmetic mean roughness Ra of the outer surface of the first layer was measured using an AFM manufactured by Oxford Instruments under the following measurement conditions. Probe: AC160TS-C3 (tip curvature R: less than 7 nm, spring constant: 26 N / m) Measurement mode: AC-Air Scan Rate: 1Hz The average roughness of the interface between the first layer and the intermediate layer was measured using a measuring device JSM-IT700HR manufactured by JEOL Ltd. under measurement conditions in accordance with JIS B0633:2001.

[0063] The evaluation criteria for the average roughness of the interface are as follows. The results are shown in Table 1. A: Average roughness is 3μm or less B: Average roughness is more than 3 μm and less than 5 μm F: Average roughness is over 5 μm

[0064] The evaluation criteria for the arithmetic mean roughness Ra are as follows. The results are shown in Table 1. A: Ra is 3μm or less B:Ra is more than 3μm and less than 5μm F: Ra is over 5 μm

[0065] The oxygen permeability coefficient of the obtained sheet was measured by the above-mentioned method using SuperDetect manufactured by MORESCO Corporation. The evaluation criteria for oxygen barrier properties are as follows. The results are shown in Table 1. A: Oxygen permeability coefficient is 1.5 x 10 5 cm 3 cm / (cm 2 ·S·Pa) or less B: Oxygen permeability coefficient is 1.5 x 10 5 cm 3 cm / (cm 2 ·S·Pa) super, 2.0×10 5 cm 3 cm / (cm 2·S·Pa) or less F: Oxygen permeability coefficient is 2.0 x 10 5 cm 3 cm / (cm 2 ·S·Pa) super

[0066] [Table 1]

[0067] The sheets of Examples 1 to 12, which had a first layer containing a polyamide resin, a second layer containing a perfluoropolymer that contains units based on tetrafluoroethylene and is melt-formable, and an intermediate layer containing a fluororesin having adhesive functional groups, and in which the average roughness of the interface between the first layer and the intermediate layer was 5 μm or less, had excellent gas barrier properties. Examples 13 to 16 in which the average roughness of the interface between the first layer and the intermediate layer exceeded 5 μm were poor in gas barrier properties.

Claims

1. A first layer containing a polyamide-based resin; a second layer containing a perfluoropolymer that includes units based on tetrafluoroethylene and is melt-fabricable; and an intermediate layer containing a fluororesin having an adhesive functional group, A sheet, wherein the average roughness of the interface between the first layer and the intermediate layer is 5 μm or less.

2. The sheet according to claim 1 , wherein the outer surface of the first layer has an arithmetic mean roughness Ra of 5 μm or less.

3. The sheet according to claim 1 or claim 2, having an average total thickness of from 1 μm to 3 mm.

4. 3. The sheet according to claim 1, wherein the adhesive functional group is at least one selected from the group consisting of a carbonyl group-containing group, a hydroxy group, an epoxy group, an amide group, an amino group, an isocyanate group, a glycidyl group, a cyano group, a silyl group, and a silanate group.

5. The sheet according to claim 1 or 2, wherein the polyamide-based resin comprises at least one selected from the group consisting of polyamide 6, polyamide 12, and a polyamide 6 / polyamide 12 copolymer.

6. The perfluoropolymer has a main chain carbon number of 1×10 6 3. The sheet according to claim 1 or claim 2, wherein the number of adhesive functional groups per unit area is 50 or less.

7. 3. The sheet according to claim 1 or 2, wherein the ratio of the average thickness of the first layer to the average total thickness of the sheet is from 0.30 to 0.

80.

8. The method for producing a sheet according to claim 1 or 2, wherein the melt constituting the first layer, the melt constituting the intermediate layer, and the melt constituting the second layer are co-extruded from a die.

9. 9. The method for producing a sheet according to claim 8, wherein the temperature of the die is set to a temperature equal to or higher than the highest melting point among the melting point of the perfluoropolymer, the melting point of the polyamide resin, and the melting point of the fluororesin having an adhesive functional group, and the difference from the highest melting point is within 50°C.

10. The method for producing a sheet according to claim 8, wherein the cooling rate is 5 to 35° C. / sec.

Citation Information

Patent Citations

  • Polyamide resin composition

    JP2012077193A